Value-oriented approach in Kazakhstani regional development projects - Shynar Uzakova; Serik Beimenbetov; Yerlan Shildibekov (Problems and Perspectives in Management, 2021)
Sustainable regional development projects are a challenge for all countries, regardless of their geographic location, cultural differences, or level of economic development. Kazakhstan is also facing this challenge and tries to counteract this process by actively implementing regional development projects and programs. However, project effectiveness and project value remain bottlenecks as these projects are aimed to improve lives and work in rural areas and eliminate inequality; therefore, managing such projects is a complex issue. This study seeks to obtain data that will help to address these research gaps and to identify value aspects of such projects from the end-users’ perspectives – local communities. This can help to understand how to select projects with high value and enhance their effectiveness.For this purpose, in 2020, a questionnaire survey and semi-structured interviews of end-users of regional development projects implemented in local communities were conducted. 301 respondents from main mining towns included in the regional development program of the Republic of Kazakhstan have been surveyed and 18 deep interviews have been conducted. The results show that Kazakhstani regional development projects appear to have a low level of value from the perspective of main stakeholders and beneficiaries – local communities. Project value evaluation has also revealed that a concept of value is different for local government authorities, project teams, and local communities. The study expands knowledge on the management of regional development projects, revealing the importance of understanding the value for such projects to achieve success and enhance their effectiveness.